Polymerase chain reaction in the identification of periodontopathogens: A reliable and satisfactory method? - Nikolić-Jakoba Nataša (Archives of Biological Sciences, 2012)
Aggregatibacter actinomycetemcomitans is considered one of the bacterial species of etiological importance in periodontitis. The aim of this study was to evaluate the serotype of A. actinomycetemcomitans in the subgingival biofilm in subjects with periodontal health and disease. Pooled samples of subgingival plaque were taken for culture-based identification of microorganisms. Colonies suspected to be A. actinomycetemcomitans were selected for molecular identification using either multiplex or conventional PCR in serotype-specific genotyping and 16S rRNA gene sequencing. In silico analysis showed that most selected colonies belong to the genus Campylobacter, although positive signals for serotypes of A. actinomycetemcomitans were obtained with these samples. Identification of A. actinomycetemcomitans by conventional PCR for 16S rRNA with one species-specific and one universal primer was inconclusive because an almost identical signal with Campylobacter gracilis was obtained. Although PCR-based methods for the identification of A. actinomycetemcomitans are more rapid, sequencing should not be omitted. [Projekat Ministarstva nauke Republike Srbije, br. 41008 and br. 173048]